2017
DOI: 10.1016/j.jpubeco.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Compulsory voting, turnout, and government spending: Evidence from Austria

Abstract: We study a unique quasi-experiment in Austria, where compulsory voting laws are changed across Austria's nine states at different times. Analyzing state and national elections from 1949-2010, we show that compulsory voting laws with weakly enforced fines increase turnout by roughly 10 percentage points. However, we find no evidence that this change in turnout affected government spending patterns (in levels or composition) or electoral outcomes. Individual-level data on turnout and political preferences sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 51 publications
(34 reference statements)
5
36
1
Order By: Relevance
“…Analyzing the state and Republican elections of 1949-2010 in Austria, it can be concluded that legal norms providing for compulsory voting with weakly executed penalties in the form of fines increase the turnout by about 10 percentage points [3]. A similar conclusion also follows from the analysis of the statistics of participation in the elections of citizens of Belgium and Italy.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Analyzing the state and Republican elections of 1949-2010 in Austria, it can be concluded that legal norms providing for compulsory voting with weakly executed penalties in the form of fines increase the turnout by about 10 percentage points [3]. A similar conclusion also follows from the analysis of the statistics of participation in the elections of citizens of Belgium and Italy.…”
Section: Resultsmentioning
confidence: 58%
“…Elections at which a mandatory vote is established are not an ideal indicator of the true preferences of the population [12]. The obligation to vote influences, above all, the turnout of those citizens who are not informed, who have no or minimal interest in politics [15].There is empirical evidence that richer economic classes have a higher level of political participation. Forced voting can be a useful mechanism for equalizing the percentage ratio of voter turnout between rich and poor [16].…”
Section: Resultsmentioning
confidence: 99%
“…Compulsory voting's upward impact on participation levels out inequities in turnout, thus increasing the proportion of the voting population that is of low socioeconomic status—and less engaged with politics (e.g., Dassonneville, Hooghe, and Miller ; Hoffman, León, and Lombardi ; Jaitman ; Singh ). Yet, at the same time, compulsory voting may tackle disengagement.…”
Section: How Compulsory Voting Affects Parties’ Vote‐seeking Strategiesmentioning
confidence: 99%
“…5; Blais ; Cancela and Geys ) and makes the voting population more reflective of the electorate (e.g., Dassonneville, Hooghe, and Miller ; Hoffman, León, and Lombardi ; Jaitman ; Singh ). There is also a burgeoning literature on the effects of compulsory voting on vote choices (e.g., Dassonneville et al., forthcoming; Dassonneville Hooghe, and Miller ; Katz and Levin, ; Selb and Lachat ; Singh , forthcoming‐b), the success of the left and right (e.g., Bechtel, Hangartner, and Schmid ; Birch , 120–28; Fowler ; Hoffman, León, and Lombardi ; Miller and Dassonneville ), political sophistication (e.g., Birch , chap. 4; Córdova and Rangel ; de Leon and Rizzi ; León ; Loewen, Milner, and Hicks ; Sheppard ; Shineman ), and attitudes toward democracy (e.g., Birch , 112–15; Singh, forthcoming‐a).…”
mentioning
confidence: 99%
“…Voter turnout in municipal and provincial elections increases by around 1.27 and 1.43 percentage points (between a quarter and a third of a standard deviation) if the number of entailed farms per 100 inhabitants 1 New studies examine how electoral institutions such as compulsory voting, opening hours of polling stations and prepaid postage influence voter turnout (e.g. Garmann 2017;Hoffman et al 2017;Schelker and Schneiter 2017;Bechtel et al 2018;Gaebler et al 2020; Potrafke and Roesel 2020). 2 Average SVP vote shares have constantly been below the 50 percent-threshold since 2010.…”
Section: Introductionmentioning
confidence: 99%